CXCL5: A coachman to drive cancer progression - Deng, Jie; Jiang, Rongqi; Meng, Enqing; Wu, Hao (Frontiers in Oncology, 2022)
Chemokines are a class of pro-inflammatory cytokines that can recruit and activate chemotactic cells. C‐X‐C motif chemokine ligand 5 (CXCL5) is a member of the chemokine family binding CXCR2 (C-X-C Motif Chemokine Receptor 2), a G-protein coupled receptor. Accumulated evidence has shown that dysregulated CXCL5 participates in tumor metastasis and angiogenesis in human malignant tumors. In this review, we summarized the advances in research on CXCL5, including its dysregulation in different tumors and the mechanism associated with tumor behavior (formation of the immunosuppressive microenvironment, promotion of tumor angiogenesis, and metastasis). We also summarized and discussed the perspective about the potential application of CXCL5 in tumor therapy targeting the tumor inflammatory microenvironment.